Iowa Birdline update, February 8, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for February 8, 1993. Highlights of the update include sightings of Golden Eagles, a Prairie Falcon, two Townsend's Solitaire and an Iceland Gull. Also included are handwritten notes for the next week's update with sightings of a Hermit Thrush in a pine plantation that was sustaining itself on bittersweet berries. Epson - sheet feed/flatbed